Analysis of the Semiotic Meaning of the Procession and Offerings of the Tradition of Ruwatan for a Single Girl at Pre-wedding Ceremonies in Javanese Society from the Perspective of Islamic Religion in Pematang Tatal Village, Serdang Bedagai Regency - Diah Safitri; Rahmat Kartolo; Sutikno Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
There is an opinion that considers that this Ruwatan tradition is a tradition of shirk people or can be said to believe in something other than Allah SWT. Problem formulation: (1). What is the traditional procession of ruwatan for a single girl? What is the semiotic meaning of the procession and offerings of the Ruwatan tradition for single girls at pre-wedding ceremonies in Javanese society, seen from an Islamic religious perspective in Pematang Tatal Village? This research is a qualitative descriptive study using a phenomenological approach. The research was carried out from October 2023 to January 2024 and was carried out in Pematang Tatal Village, Perbaungan District, Serdang Bedagai Regency. Techniques for collecting data to obtain the desired data, researchers use several methods, namely: (a). observation; (b). interview or interview; and (c) documentation. Data processing methods are: a. data check (editing); b. classification (classifying); c. verification (verifying); d. analysis (analyzing); e. conclusion (concluding). The study analyzes the semiotic meaning of various Ruwatan tradition ceremonies, including Sungkeman, Siraman, Haircut, Tirakatan, and Thanksgiving Prayer. The tradition is part of the Koran teachings for Muslims. Three opinions exist: opposition, pro, and tolerant. Opponents view it as a polytheistic Javanese custom, proponents preserve it as cultural heritage, and tolerants acculturate it to Islamic values.